2020
DOI: 10.1149/1945-7111/ab7368
|View full text |Cite
|
Sign up to set email alerts
|

Moving Boundary Simulation of Iron-Zinc Sacrificial Corrosion under Dynamic Electrolyte Thickness Based on Real-Time Monitoring Data

Abstract: The electrolyte film thickness condensation and evaporation is an important parameter for complexity of atmospheric corrosion. Atmospheric corrosion rate of zinc at the west coast of Singapore was measured for one year using an electrical resistance monitoring system. The analysis of the data reveals that significant corrosion rates only occur at specific hours on dry days. The beginning of this period corresponds to falling temperature and rising relative humidity resulting in the formation of a film of moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Their simulation results showed that the maximum corrosion rate occurs at an electrolyte thickness of about 8 µm, which is very close to the 10 µm value obtained by Simillion et al [18]. Moreover, the simulation of Saeedikhani et al [11] suggested that a cut-edge is a more severe defect than a scratch, with this being confirmed by the appearance of iron corrosion products on atmospheric exposed cut-edge samples whereas scratched samples were not corroded after one week of exposure. However, although their time-dependent model was able to depict the accumulation (growth) of a corrosion product layer, it considered Zn(OH) 2 as the only precipitating corrosion product.…”
Section: The Current Status Of Fem Thin Film Corrosion Modelling: Where We Advanced?supporting
confidence: 73%
See 2 more Smart Citations
“…Their simulation results showed that the maximum corrosion rate occurs at an electrolyte thickness of about 8 µm, which is very close to the 10 µm value obtained by Simillion et al [18]. Moreover, the simulation of Saeedikhani et al [11] suggested that a cut-edge is a more severe defect than a scratch, with this being confirmed by the appearance of iron corrosion products on atmospheric exposed cut-edge samples whereas scratched samples were not corroded after one week of exposure. However, although their time-dependent model was able to depict the accumulation (growth) of a corrosion product layer, it considered Zn(OH) 2 as the only precipitating corrosion product.…”
Section: The Current Status Of Fem Thin Film Corrosion Modelling: Where We Advanced?supporting
confidence: 73%
“…Our paper is focused explicitly on FEM for thin film (and extremely thin film) corrosion, applicable to atmospheric corrosion, in a very concise and straightforward manner-taking into account only the highlighted works in this field and discussing them in a different perspective than in reference [9]. In addition, an essential contribution in this field was on FEM moving boundary simulation [10,11] that was published after the review of Liu and Kelly, which is included here. Incorporation of the concept of a moving boundary in FEM corrosion modelling will be crucial for future research directions, as will be explained in Section 3.…”
Section: The Current Status Of Fem Thin Film Corrosion Modelling: Where We Advanced?mentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of studies in the literature carried out steady-state modeling of cathodic protection, Saeedikhani et al . 12 , 13 published studies on time-dependent behavior of zinc deformation/consumption in galvanized steel using the moving boundary simulation method. Sun et al .…”
Section: Introductionmentioning
confidence: 99%
“…current density distribution 11 . While the majority of studies in the literature carried out steady-state modeling of cathodic protection, Saeedikhani et al 12,13 published studies on time-dependent behavior of zinc deformation/consumption in galvanized steel using the moving boundary simulation method. Sun et al 14 adapted an Arbitrary Lagrangian-Eulerian (ALE) numerical model for the time-dependent evolution of crevice corrosion.…”
mentioning
confidence: 99%